Reproductive features and use of an anti-inflammatory drug in estrus-induced dairy goats artificially inseminated in a standing position with cervix immobilization - Fonseca, Jeferson Ferreira; Alvim, Gilmar Pereira; Goncalves Souza-Fabjan, Joanna Maria; Franco Oliveira, Maria Emilia [UNESP]; Brair, Viviane Lopes; Brandao, Felipe Zandonadi; Faco, Olivardo (Inst Animal Reproduction Food Research, 2017)
This study evaluated reproductive features and role of Flunixin-Meglumine at timed artificial insemination (AI), using a new technique of standing position with cervix immobilization. In Experiment 1, 10 goats (n = 5 nulliparous [Null] and 5 pluriparous [Plu]) were evaluated after estrus induction by recorded reproductive parameters to define the ideal time for AI. In Experiment 2, goats were artificially inseminated 51-54 h after sponge removal with frozen-thawed semen. At AI, 1 mL saline (CONTROL; 18 Null and 14 Plu) or 50 mg Flunixin-Meglumine (FLUNIXIN; 15 Null and 18 Plu) was administered i.m. Location of semen deposition was recorded for both groups. In Experiment 1, all sexual behavior and ovulatory parameters were similar between Null and Plu for estrus response and ovulation (100%), interval from sponge removal to ovulation (similar to 64.2 h), largest ovulatory follicle diameter (similar to 6.6 mm), and number of ovulations (similar to 2.0). In Experiment 2, pregnancy rate was superior (P < 0.01) for CONTROL (62.5%; 10 Null and 10 Plu) than FLUNIXIN (30.3%; 3 Null and 7 Plu) goats. Regardless of the treatment, intrauterine AI was more frequent (P < 0.01) in Plu (100.0%; 32/32) than in Null (69.7%; 23/33) goats. Moreover, AI was more time-consuming (P < 0.01) in Null (44 +/- 37 s; 4-139 s) than in Plu (21 +/- 19 s, 4-78 s) goats. Therefore, administration of Flunixin-Meglumine at the time of AI adversely affected pregnancy rate. High rates of intrauterine cervical penetration were obtained, achieving good pregnancy rates in goats not receiving Flunixin-Meglumine. 2017 Society for Biology of Reproduction & the Institute of Animal Reproduction and Food Research of Polish Academy of Sciences in Olsztyn. Published by Elsevier Sp. z o.o. All rights reserved.
Keywords: Artificial insemination; Al technique; Caprine; Fertility; Ovulation